DAVID DOWELL CUSIC AND THE LINGUISTIC STUDY OF REPETITION: A FOUNDATIONAL APPROACH TO VERBAL PLURALITY AND ASPECT - Khabibullina Liliya Jakhonovna (Bright Mind Publishing, 2025)
This article provides a comprehensive exploration of David Dowell Cusic's seminal work on verbal plurality and its relevance to the broader linguistic study of repetition and aspect. Cusic's 1981 dissertation, "Verbal Plurality and Aspect", laid the groundwork for understanding how languages morphosyntactically and semantically encode repeated and distributed events. His classification of verbal plurality—event-internal, event-external, and participant plurality—continues to serve as a critical framework for typologists, semanticists, and syntacticians investigating aspect and event structure across languages.